Electoral Institutions and the Emergence of Terrorist Groups. Issue 1 (31st October 2012) - Aksoy, Deniz; Carter, David B.
<x content-type="archive" xml:space="preserve">Abstract</x> A wide range of studies find that democracies experience more terrorism than non-democracies. However, surprisingly little terrorism research takes into account the variation among democracies in terms of their electoral institutions. Furthermore, despite much discussion of the differences in terrorist groups' goals in the literature, little quantitative work distinguishes among groups with different goals, and none explores whether and how the influence of electoral institutions varies among groups with different goals. The argument in this article posits that electoral institutions influence the emergence of within-system groups, which seek policy changes, but do not influence the emergence of anti-system groups, which seek a complete overthrow of the existing regime and government. The study finds that within-system groups are significantly less likely to emerge in democracies that have a proportional representation system and higher levels of district magnitude, while neither of these factors affects the emergence of anti-system groups.